Protective Effect of Siegesbeckia orientalis on Pancreatic β-Cells under High Glucose-Induced Glucotoxicity - Chi-Chang Chang (MDPI AG, 2021)
The glucotoxicity caused by long-term exposure of β-cells to high glucose (HG) conditions may lead to the generation of more reactive oxygen species (ROS), reduce the activity of antioxidant enzymes, cause cell damage and apoptosis, and induce insulin secretion dysfunction. Siegesbeckia orientalis linne is a traditional folk herbal medicine used to treat snake bites, rheumatoid arthritis, allergies, and immune deficiencies. In this study, we evaluated the protective effect of S. orientalis ethanol extract (SOE) on cell death and oxidative stress in RIN-m5f pancreatic β-cells stimulated by two HG concentrations (50–100 mM). In the cell viability assay, SOE could significantly increase the survival rate of pancreatic β-cells under HG-induced conditions. For the oxidative stress induced by HG condition, the treatment of SOE effectively reduced the ROS formation, increased the content of intracellular glutathione, and up-regulated the expression of antioxidant enzymes, catalase, superoxide dismutase, and glutathione peroxidase. As a result, the SOE treatment could decrease the glucotoxicity-mediated oxidative damage on RIN-m5F β-cells. Moreover, SOE had the function of regulating insulin secretion in pancreatic β-cells under different HG-mediated conditions. It could decrease the increasing intracellular insulin secretion under the low glucose concentration to normal level; while increase the decreasing intracellular insulin secretion under the relatively high glucose concentration to normal level. Taken together, this study suggests that SOE has a protective effect on pancreatic β-cells under the HG-stimulated glucotoxic environment.